Emphysematous cystitis: A case report. - Siriboonrid, Satit; Kanjanatarayon, Sarayut; Jiraanankul, Vittaya; Wiriyabanditkul, Weerayut; Binsri, Nattapong (Insight Urology, 2019)
Infection is a serious problem encountered in urology, especially when emergency or severe conditions fail to respond to medications or conservative treatment. Emphysematous cystitis is a rare condition, and thus rapid, correct management is important. In this report, we review our experience and the steps of treatment for this rare condition.